QSAR Modeling of Compounds Derived from 1,2,3-Triazolopiperidine as DPP-4 Enzyme Inhibitors Using Semiempirical AM1 - Anjar Purba Asmara; Reni Silvia Nasution; Rosi Minarty (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
This study aims to model the derived compounds of 1,2,3-triazolopiperidine using semiempirical method AM1 and determine the further derivation with the better IC50 values against DPP-4 enzyme theoretically. This research employed ChemDraw Pro 12 software for for 2D structural drawing, Hyperchem 8.0 for 3D modelling, and MLR statistical analysis for modeling QSAR equations. The semiempirical method was likely to be the appropriate platform to apply because the correlation coefficient of H1 NMR chemical shift between theoretical and actual value is relatively close, 0.8891. The multilinear regression analysis produced 4 equation models where the best one is equation 4 as detailed below:” IC50 = 875,5116 + (-7400,27*qH35) + (-0,00133* Eat.is) + (-3230,72* qN23) + (3,30277* µ)” n = 25; r2 = 0,594; Adjusted r2= 0,486; PRESS = 1,2× 104. Finally, the theoretically promising substituent was -CN possessing IC50 value = 1.61 nM.